An Instrumented Minimally Invasive Surgical Tool: Design and Calibration. Issue 2 (19th September 2011) - Roan, Philip R.; Wright, Andrew S.; Lendvay, Thomas S.; Sinanan, Mika N.; Hannaford, Blake
Abstract : Minimally invasive surgical procedures have improved the standard of patient care by reducing recovery time, chance of infection, and scarring. A recent review estimates that leaks occur in 3% to 6% of bowel anastomoses, resulting in "increased morbidity and mortality and adversely [affecting] length of stay, cost, and cancer recurrence" [23]. Many of these leaks are caused by poor handling and ischemic tissue. Detecting a change in temperature can indicate ischemic tissue. The optical absorption spectrum of a tissue can be used to detect tissue oxygen concentration and tissue ischemia. The electrical impedance of tissue changes as ischemia progresses. This article describes the development of a minimally invasive surgical tool with integrated sensors for replicating ischemia detection measurements during routine manipulation of the tissue. To be useful, this tool should be feasible for use in a real operating room, providing real-time feedback and diagnosis to the surgeon. The design of the tool and choice of the sensors leverages existing work in physiological measurements and surgical tool design. The tool includes a thermistor for measuring the temperature, four LEDs and a photodiode for measuring local optical absorption, and four electrodes for measuring the electrical impedance. The sensors are located on a 7 mm square sensor head, which is mounted to a minimally invasive grasper. A strain gauge and optical encoder monitor the applied force and position of the tool, and a motor controls both. This allows the tool to control the tool-tissue interface. Sensor accuracy has been validated through calibration.